Are Urban Slum Dwellers Aware About Tuberculosis? – A Cross Sectional Study in Surat City - Mahida, Hetvi D; Shroff, Kavin N; Kesur, Tanvi D; Patel, N B (National Journal of Community Medicine, 2014)
Introduction: The global burden of TB mainly lies in the 22 high burden countries and about 50% of prevalence occurs in 5 countries of South East Asia, namely, India, Indonesia, Bangladesh, and Thailand, Myanmar. Perceptions regarding TB prevailing in the community inﬂuence the health seeking behavior of the community. It is important that basic knowledge about the disease and the availability of treatment is clear among community to prevent any undue delay in availing the service. Methodology: A community-based cross-sectional study was conducted in urban slum in catchment area of urban health training centre, Varachha of the Surat District. A pretested, structured interview schedule was used to assess the KAP related to symptoms, causes, spread, and treatment of TB. Domains identified were knowledge about TB, symptoms, spread, diagnosis, treatment, and prevention of TB. Result: According to participants view in relation to presenting symptoms it can be fever (84.4%), cough >14 days (66.2%), weight loss (69.72%), and hemoptysis (23.85%). Out of 218, 126 (57.8%) participants believed that TB can be transmitted through sneezing/ cough. But only 51.83% were aware about correct duration of treatment. 129 (59.17%) had knowledge regarding place of treatment for TB. Conclusion: Knowledge about symptoms and treatment of tuberculosis among respondents was quite good; however, misconceptions about transmission of disease lead to discrimination. Knowledge about “free treatment” and “duration of treatment” has to be stressed during health education activities.